The role of Doppler ultrasonography in vascular access surveillance—controversies continue. Issue 1 (November 2021) - Malik, Jan; Lomonte, Carlo; Meola, Mario; de Bont, Cora; Shahverdyan, Robert; Rotmans, Joris I; Saucy, Francois; Jemcov, Tamara; Ibeas, Jose
Chronic hemodialysis therapy required regular entry into the patient's blood stream with adequate flow. The use of arteriovenous fistulas and grafts is linked with lower morbidity and mortality than the use of catheters. However, these types of accesses are frequently affected by stenoses, which decrease the flow and lead to both inadequate dialysis and access thrombosis. The idea of duplex Doppler ultrasound surveillance is based on the presumption that in-time diagnosis of an asymptomatic significant stenosis and its treatment prolongs access patency. Details of performed trials are conflicting, and current guidelines do not support ultrasound surveillance. This review article summarizes the trials performed and focuses on the reasons of conflicting results. We stress the need of precise standardized criteria of significant access stenosis and the weakness of the metaanalyses performed.